2014
DOI: 10.1016/j.nbd.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic inhibition of chemically induced hypersynchronized bursting in mice

Abstract: Synchronized activity is common during various physiological operations but can culminate in seizures and consequently in epilepsy in pathological hyperexcitable conditions in the brain. Many types of seizures are not possible to control and impose significant disability for patients with epilepsy. Such intractable epilepsy cases are often associated with degeneration of inhibitory interneurons in the cortical areas resulting in impaired inhibitory drive onto the principal neurons. Recently emerging optogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 41 publications
4
32
0
1
Order By: Relevance
“…Global activation of various populations of inhibitory interneurons could produce prolonged suppression of epileptiform activity during light stimulation (29). Direct hyperpolarization of the principal cells through chloride channel could be responsible for the suppressive effects (30). However, similar to a previous study (30), longer duration of light exposure for global activation of interneurons reduced the suppressive effects…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global activation of various populations of inhibitory interneurons could produce prolonged suppression of epileptiform activity during light stimulation (29). Direct hyperpolarization of the principal cells through chloride channel could be responsible for the suppressive effects (30). However, similar to a previous study (30), longer duration of light exposure for global activation of interneurons reduced the suppressive effects…”
Section: Discussionmentioning
confidence: 99%
“…Direct hyperpolarization of the principal cells through chloride channel could be responsible for the suppressive effects (30). However, similar to a previous study (30), longer duration of light exposure for global activation of interneurons reduced the suppressive effects…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, a recent study has used an optic fiber attached to a metal electrode and a glass capillary for the delivery of a solution containing a selective GABA A receptor antagonist ( i.e. bicuculline methiodide) to the opsin-transfected population (Berglind et al, 2014). Though successful, this route of drug delivery suffers from a number of potential drawbacks, including (i) mechanical instability of the neuronal tissue at the time of injection (with chances of loosing the recorded neurons and thus eliminating the possibility of recording the same neurons before and during drug application), (ii) delivery of an unknown drug concentration at, and around, the site of injection, and (iii) poor control of the spatial extent of drug action.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the repertoire of optogenetic tools is ever expanding to include opsins with altered ion specificity and increased effectiveness (Berndt et al 2014;Chuong et al 2014), and this technology is being used to research possible treatments for a multitude of neurological disorders, including epilepsy, Parkinson's disease, and Alzheimer's disease (Gradinaru et al 2009;Krook-Magnuson and Soltesz 2015;Yamamoto et al 2015). By using optogenetics to control the activity of specific circuits, important discoveries have been made regarding the circuits involved in epileptiform activity in in vitro and in vivo seizure or epilepsy models (Tønnesen et al 2009;Kokaia 2011;Wykes et al 2012;Armstrong et al 2013;Krook-Magnuson et al 2013Paz et al 2013;Rossignol et al 2013;Sukhotinsky et al 2013;Berglind et al 2014;Ledri et al 2014). Soon after early experiments showing optogenetic control of seizure-like events in hippocampal culture preparations (Tønnesen et al 2009), several in vivo studies showed that optogenetics can be used to manipulate specific neuronal circuits within rodent models of epilepsy to control seizures (Wykes et al 2012;Armstrong et al 2013;Krook-Magnuson et al 2013Paz et al 2013).…”
Section: Optogenetic Targeting Of Specific Circuits In Epilepsy Applimentioning
confidence: 99%